Mosaic Arrangement of the 5S rDNA in the Aquatic Plant Landoltia punctata (Lemnaceae) - Chen, Guimin; Stepanenko, Anton; Borisjuk, Nikolai (Frontiers in Plant Science, 2021)
Duckweeds are a group of monocotyledonous aquatic plants in the Araceae superfamily, represented by 37 species divided into five genera. Duckweeds are the fastest growing flowering plants and are distributed around the globe; moreover, these plants have multiple applications, including biomass production, wastewater remediation, and making pharmaceutical proteins. Dotted duckweed (Landoldtia punctata), the sole species in genus Landoldtia, is one of the most resilient duckweed species. The ribosomal DNA (rDNA) encodes the RNA components of ribosomes and represents a significant part of plant genomes, but has not been comprehensively studied in duckweeds. Here, we characterized the 5S rDNA genes in L. punctata by cloning and sequencing 25 PCR fragments containing the 5S rDNA repeats. No length variation was detected in the 5S rDNA gene sequence, whereas, the non-transcribed spacer (NTS) varied from 151 to 524 bp. The NTS variants grouped into two major classes, which differed both in nucleotide sequence and the type and arrangement of the spacer subrepeats. The dominant class I NTS, with a characteristic 12-bp TC-rich sequence present in 3 to 18 copies, was classified into four subclasses, whereas the minor class II NTS, with shorter, 9-bp nucleotide repeats, was represented by two identical sequences. In addition to these diverse subrepeats, class I and class II NTSs differed in their representation of cis-elements and the patterns of predicted G-quadruplex structures, which may influence the transcription of the 5S rDNA. Similar to related duckweed species in the genus Spirodela, L. punctata has a relatively low rDNA copy number, but in contrast to Spirodela and the majority of other plants, the arrangement of the 5S rDNA units demonstrated an unusual, heterogenous pattern in L. punctata, as revealed by analyzing clones containing double 5S rDNA neighboring units. Our findings may further stimulate research on the evolution of plant rDNA and discussion of the molecular forces driving homogenization of rDNA repeats in concerted evolution.